Diagnosis and surgical approach of adult Hirschsprung's disease: About two observations and review of the literature. Case series. (December 2019) - Adamou, Harissou; Amadou Magagi, Ibrahim; Habou, Oumarou; Adakal, Ousseini; Aboulaye, Maman Bachir; Robnodji, Alliance; James Didier, Lassey; Sani, Rachid; Abarchi, Habibou
Abstract: Introduction: Hirschsprung's disease (HD) is uncommon in adulthood. In this study, we describe the management of two cases of adult Hirschsprung's disease treated with transanal colonic pull-through procedure followed by a delayed coloanal anastomosis. Patients and methods: This was a retrospective (December 2016 to Jun 2019) study included two cases of adult HD with confirmed Hirschsprung disease who underwent surgery at Zinder National hospital, Niger. The registration number is researchregistry 5174. Results: These were two patients aged 21 years (male) and 22 years (female) admitted to the emergency department with an acute bowel obstruction. The history finds a delayed passage of meconium at birth with a history of long-standing recurrent constipation since early childhood for the 2 patients. A lateral colostomy was performed urgently in both patients and the barium enema revealed a disparity of the sigmoid colon with corn shaped transition zone. Histologic examination of the biopsy specimen confirmed the diagnosis of HD. Surgery was done according to transanal endorectal pull-through procedure followed by delayed coloanal anastomosis. Patients were regularly followed over a period of 16 months. Constipation was gone, no continence problem was reported and quality of life was rated satisfactory. Conclusion: The discovery of Hirschsprung's disease is rare in adulthood. Transanal endorectal pull-through procedure followed by delayed coloanal anastomosis with conventional surgery is a suitable option for the treatment of HD and gives a good result. Highligths: More than 90% of cases, diagnosis and treatment of Hirschsprung's disease are made in the first 5 years of life; as a result, the diagnosis of HD in adulthood is rare. Surgical treatment in adulthood is more laborious because of anatomical changes. Many surgical procedures have been described, the best known of which are Swenson, Duhamel, Soave and Lynn. Modifications of these techniques have been proposed. The goal of surgical treatment is to resect or exclude the aganglionic segment and to lower the healthy colon, normally innervated at the anus. Transanal colonic pull-through procedure followed by a delayed coloanal anastomosis with conventional surgery and manual anastomosis, gives satisfactory results and remains well adapted to the adult Hirschsprung's disease in context of limited resources.